Hindered nematic alignment of hematite spindles in poly(N‐isopropylacrylamide) hydrogels: a small‐angle X‐ray scattering and rheology study. Issue 1 (3rd January 2018) - Nack, Annemarie; Seifert, Julian; Passow, Christopher; Wagner, Joachim
Abstract : Nematic order parameters and orientational distribution functions of anisotropic magnetic hematite particles suspended in water and embedded in different poly( N ‐isopropylacrylamide) hydrogels are determined by means of small‐angle X‐ray scattering. Owing to particle–matrix interactions, the field‐induced nematic alignment of the particles is progressively hindered by the increasing elasticity of the polymer network. Abstract : Field‐induced changes to the mesostructure of ferrogels consisting of spindle‐shaped hematite particles and poly( N ‐isopropylacrylamide) are investigated by means of small‐angle X‐ray scattering (SAXS). Related field‐induced changes to the macroscopic viscoelastic properties of these composites are probed by means of oscillatory shear experiments in an external magnetic field. Because of their magnetic moment and magnetic anisotropy, the hematite spindles align with their long axis perpendicular to the direction of an external magnetic field. The field‐induced torque acting on the magnetic particles leads to an elastic deformation of the hydrogel matrix. Thus, the field‐dependent orientational distribution functions of anisotropic particles acting as microrheological probes depend on the elastic modulus of the hydrogel matrix. The orientational distribution functions are determined by means of SAXS experiments as a function of the varying flux density of an external magnetic field. With increasing elasticity of the hydrogels, tuned via the polymer volume fraction and the crosslinking density, the field‐induced alignment of these anisotropic magnetic particles is progressively hindered. The microrheological results are in accordance with macrorheological experiments indicating increasing elasticity with increasing flux density of an external field.